Is environmentally induced income variability a driver of human migration?*. (2nd January 2017) - Marchiori, Luca; Maystadt, Jean-François; Schumacher, Ingmar
Abstract : The role of environmentally induced income variability as a determinant of migration has been studied little to none. We provide a theoretical discussion based on a 'risk aversion channel' and an overview of the empirical literature on this. We also extend a previous empirical study on 39 sub-Saharan African countries with yearly data from 1960 to 2000 by including income variability and its weather determinants. Our findings lead us to acknowledge that, based on our dataset and methodology, income variability is a negligible driver of migration decisions at the macroeconomic level.